Final height of patients who underwent bone marrow transplantation during childhood. Issue 5 (May 1996) - Cohen, A; Rovelli, A; Van-Lint, M T; Uderzo, C; Morchio, A; Pezzini, C; Masera, G; Bacigalupo, A; Romano, C
Abstract : OBJECTIVE: To determine the impact on final adult height of bone marrow transplantation. METHODS: The final height of 28 long term survivors (18 males; 10 females), allografted before or at the onset of puberty, at a median age of 10.8 years (range 6.3 to 14.6) and who did not receive growth hormone (GH) treatment or other growth promoting agents, was evaluated. Median follow up period after bone marrow transplantation was 7.9 years (range 3.2 to 11.4), and age at the most recent evaluation 18.1 years (range 15.6 to 24.5). Height values were expressed in standard deviation score (SDS) from the mean of the normal population. Height at bone marrow transplantation was compared with final height as well as with parental genetic height. Patients were divided into three groups: severe aplastic anaemia (SAA): three patients given no radiotherapy; leukaemia-total body irradiation (TBI): 14 patients with acute or chronic leukaemia conditioned with chemotherapy and TBI; leukaemia-TBI with previous cranial radiation therapy (CRT): 11 patients. None of the patients had solid tumour. RESULTS: There was a decrease in final height SDS compared to pre-transplantation height SDS (paired t test, p < 0.0001). All patients except one reached an adult height above -2.0 SDS. A significant decrease in height SDS was found in the TBI and the CRT groups (paired t test, p = 0.02 and p = 0.0002, respectively). Whereas height SDS value at the time of transplant was higher than the genetic height SDS, final height SDS values were lower. CONCLUSIONS: Despite the decrease in height SDS found after bone marrow transplantation, 27 of the 28 patients spontaneously achieved what is considered to be a normal height SDS (above -2.0 SDS). This should be taken into account when considering GH treatment in children who underwent bone marrow transplantation for malignant haematological diseases.